Unusual lung involvements of invasive mucinous adenocarcinoma with chylothorax - Ayako Aoki; Yu Hara; Koji Okudela; Yoshihiro Ishikawa; Kosei Doshita; Hisashi Hashimoto; Kentaro Nakashima; Nobuyuki Horita; Nobuaki Kobayashi; Takeshi Kaneko (Thoracic Cancer, 2020)
Abstract A 77‐year‐old man who had a persistent productive cough for one month was admitted to our hospital. Chest computed tomography (CT) revealed subpleural nodular opacities, irregular pleural thickening with bilateral basal predominance, and a small right pleural effusion. Aspirated fluid was exudative and had the appearance of chylothorax without malignant cells. Surgical lung biopsy specimen showed focal proliferation of neoplastic epithelial cells with lepidic‐predominant pattern and abundant mucus in the alveolar spaces, consistent with invasive mucinous adenocarcinoma (IMA). The results of PD‐L1 expression and the EGFR, ALK, ROS1, and BRAF mutation status analyzed by next generation sequencer were all negative. IMA should be considered in the differential diagnosis of subpleural micronodular opacities accompanied by pleural effusion (chylothorax) on chest CT. Key points Significant findings of the study This case showed subpleural micronodular opacities and chylothorax as unusual chest computed tomography (CT) patterns for invasive mucinous adenocarcinoma (IMA). What this study adds Invasive mucinous adenocarcinoma (IMA) should be considered in the differential diagnosis of subpleural micronodular opacities accompanied by pleural effusion on chest CT.